Analogs of nitrofuran antibiotics are potent GroEL/ES inhibitor pro-drugs. Issue 22 (15th November 2020) - Stevens, Mckayla; Howe, Chris; Ray, Anne-Marie; Washburn, Alex; Chitre, Siddhi; Sivinski, Jared; Park, Yangshin; Hoang, Quyen Q.; Chapman, Eli; Johnson, Steven M.
Graphical abstract: Abstract: In two previous studies, we identified compound 1 as a moderate GroEL/ES inhibitor with weak to moderate antibacterial activity against Gram-positive and Gram-negative bacteria including Bacillus subtilis, methicillin-resistant Staphylococcus aureus, Klebsiella pneumonia, Acinetobacter baumannii, and SM101 Escherichia coli (which has a compromised lipopolysaccharide biosynthetic pathway making bacteria more permeable to drugs). Extending from those studies, we developed two series of analogs with key substructures resembling those of known antibacterials, nitroxoline (hydroxyquinoline moiety) and nifuroxazide/nitrofurantoin ( bis -cyclic- N -acylhydrazone scaffolds). Through biochemical and cell-based assays, we identified potent GroEL/ES inhibitors that selectively blocked E. faecium, S. aureus, and E. coli proliferation with low cytotoxicity to human colon and intestine cells in vitro . Initially, only the hydroxyquinoline-bearing analogs were found to be potent inhibitors in our GroEL/ES-mediated substrate refolding assays; however, subsequent testing in the presence of an E. coli nitroreductase (NfsB) in situ indicated that metabolites of the nitrofuran-bearing analogs were potent GroEL/ES inhibitor pro-drugs. Consequently, this study has identified a new target of nitrofuran-containing drugs, and is the first reported instance of such a unique class of GroEL/ES chaperonin inhibitors. The intriguing results presented herein provide impetus for expanded studies to validate inhibitor mechanisms and optimize this antibacterial class using the respective GroEL/ES chaperonin systems and nitroreductases from E. coli and the ESKAPE bacteria.